Research progress on the microbial metabolism and transport of polyamines and their roles in animal gut homeostasis - Chong Zhang; Yongkang Zhen; Yunan Weng; Jiaqi Lin; Xinru Xu; Jianjun Ma; Yuhong Zhong; Mengzhi Wang (Journal of Animal Science and Biotechnology)
Abstract Polyamines (putrescine, spermidine, and spermine) are aliphatic compounds ubiquitous in prokaryotes and eukaryotes. Positively charged polyamines bind to negatively charged macromolecules, such as nucleic acids and acidic phospholipids, and are involved in physiological activities including cell proliferation, differentiation, apoptosis and gene regulation. Intracellular polyamine levels are regulated by biosynthesis, catabolism and transport. Polyamines in the body originate from two primary sources: dietary intake and intestinal microbial metabolism. These polyamines are then transported into the bloodstream, through which they are distributed to various tissues and organs to exert their biological functions. Polyamines synthesized by intestinal microorganisms serve dual critical roles. First, they are essential for maintaining polyamine concentrations within the digestive tract. Second, through transcriptional and post-transcriptional mechanisms, these microbial-derived polyamines modulate the expression of genes governing key processes in intestinal epithelial cells—including proliferation, migration, apoptosis, and cell–cell interactions. Collectively, these regulatory effects help maintain intestinal epithelial homeostasis and ensure the integrity of the gut barrier. In addition, polyamines interact with the gut microbiota to maintain intestinal homeostasis by promoting microbial growth, biofilm formation, swarming, and endocytosis vesicle production, etc. Supplementation with polyamines has been demonstrated to be important in regulating host intestinal microbial composition, enhancing nutrient absorption, and improving metabolism and immunity. In this review, we will focus on recent advances in the study of polyamine metabolism and transport in intestinal microbes and intestinal epithelial cells. We then summarize the scientific understanding of their roles in intestinal homeostasis, exploring the advances in cellular and molecular mechanisms of polyamines and their potential clinical applications, and providing a rationale for polyamine metabolism as an important target for the treatment of intestinal-based diseases. Graphical Abstract